2022
DOI: 10.3390/ijerph19052759
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic Reactions during Heart Rate Variability Biofeedback Session in Adolescents with Different Risk of Internet Addiction

Abstract: The aim of this study was to determine electroencephalogram (EEG) in a session of heart rate variability biofeedback (HRV BF) in adolescents with different Internet addiction (IA) risks. In total, 100 healthy adolescents aged 16–17 years with minimal risk of IA (Group I, 35%), pronounced risk of IA (Group II, 51%), and stable pattern of IA (Group III, 14%) using the Chen Internet Addiction Scale were examined. HRV and EEG parameters were determined at baseline (5 min), and then during the short-term HRV BF ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…People with low levels of executive functioning are vulnerable to intermittent reinforcement principles connected to internet-related activities. These processes are key factors in the transition from voluntary/goal-directed actions (with an appraisal of action consequences) to habitual actions (seemingly automatic and uncontrolled), which is at the basis of addictive behaviors [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Another model, the Interaction of Person-Affect-Cognition-Execution (I-PACE), proposes that PIU behaviors may be explained by looking at interactions between predisposing factors (e.g., impulsivity, anxiety, depression, general distress), moderators (e.g., coping style, self-regulatory capacities, and internet-related attentional and cognitive biases), and mediators such as reduced inhibitory control in combination with reduced executive functioning and diminished decision making [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…People with low levels of executive functioning are vulnerable to intermittent reinforcement principles connected to internet-related activities. These processes are key factors in the transition from voluntary/goal-directed actions (with an appraisal of action consequences) to habitual actions (seemingly automatic and uncontrolled), which is at the basis of addictive behaviors [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Another model, the Interaction of Person-Affect-Cognition-Execution (I-PACE), proposes that PIU behaviors may be explained by looking at interactions between predisposing factors (e.g., impulsivity, anxiety, depression, general distress), moderators (e.g., coping style, self-regulatory capacities, and internet-related attentional and cognitive biases), and mediators such as reduced inhibitory control in combination with reduced executive functioning and diminished decision making [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, withdrawal symptoms associated with excessive internet use had the greatest influence in reducing the HRV biofeedback efficiency during short-term training. Similarly, Demin and Poskotinova [80] compared three groups of adolescents between 16 and 17 years old at minimal risk of internet addiction, at high risk of internet addiction, and those with a diagnosis of internet addiction. Apart from HRV, they added EEG measures at baseline and during the short-term HRV biofeedback training period to identify the most sensitive brain regions to HRV biofeedback.…”
Section: Hrv Biofeedbackmentioning
confidence: 99%
“… 10 Conversely, biofeedback protocols using peripheral measurements, primarily based on heart rate variability, have centered on behavioral addictions. 11 Therefore, although there have been limited studies applying neurofeedback to internet addiction patients, research utilizing neurofeedback as an additional tool for the treatment of alcohol use disorder has demonstrated effects, influencing attentional bias or lack of inhibition. 12 Studies observing the brainwave characteristics of internet addiction have revealed shared neurophysiological traits with other addictions.…”
Section: Introductionmentioning
confidence: 99%